2009
DOI: 10.1097/crd.0b013e3181a857ba
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interaction Between Clopidogrel and Proton Pump Inhibitors

Abstract: Dual antiplatelet therapy with clopidogrel and aspirin has been shown to reduce recurrent cardiac events in patients with acute coronary syndromes or those who have undergone coronary artery stent placement. Clopidogrel, a thienopyridine, is a prodrug that is transformed in vivo to an active metabolite by the cytochrome P450 enzyme system. Due to the increased risk of bleeding in patients on dual antiplatelet therapy, concomitant gastrointestinal ulcer prophylaxis with a proton pump inhibitor (PPI) is frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…The lack of such a correlation between pharmacodynamic data and clinical outcome might be explained by various factors: (i) the hepatic cytochrome P450 2C19 (CYP2C19) is not the only active isoenzyme responsible for the conversion of thienopyridine pro‐drugs into active metabolites [59] and exhibits large genotypic differences in its expression levels [60]; (ii) PPIs are competitive inhibitors of active metabolite formation of clopidogrel and differ largely in their pharmacokinetics: omeprazole exhibits the highest potential for drug–drug interactions among PPIs, and pantoprazole the lowest [61]; (iii) if CYP2C19 is blocked, other isoenzymes such as CYP2B6 and CYP3A4 might take over the metabolic conversion [60]; (iv) the different ex vivo assay systems used at present miss acuity and comparability; (v) within these test systems the correct cut offs for the detection of a clinically important inhibition of action of thienopyridines have not been defined so far; and (vi) given the heterogeneity of the included studies the presumed contradiction may be explained by the presence of confounders and bias in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of such a correlation between pharmacodynamic data and clinical outcome might be explained by various factors: (i) the hepatic cytochrome P450 2C19 (CYP2C19) is not the only active isoenzyme responsible for the conversion of thienopyridine pro‐drugs into active metabolites [59] and exhibits large genotypic differences in its expression levels [60]; (ii) PPIs are competitive inhibitors of active metabolite formation of clopidogrel and differ largely in their pharmacokinetics: omeprazole exhibits the highest potential for drug–drug interactions among PPIs, and pantoprazole the lowest [61]; (iii) if CYP2C19 is blocked, other isoenzymes such as CYP2B6 and CYP3A4 might take over the metabolic conversion [60]; (iv) the different ex vivo assay systems used at present miss acuity and comparability; (v) within these test systems the correct cut offs for the detection of a clinically important inhibition of action of thienopyridines have not been defined so far; and (vi) given the heterogeneity of the included studies the presumed contradiction may be explained by the presence of confounders and bias in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Given recent data that raise questions regarding the risk of drug interactions between PPIs and clopidogrel [23][24][25][26] , some clinicians have advocated the use of H2RAs in patients who require chronic use of both NSAIDs and clopidogrel 24,25 . Ibuprofen and famotidine do not appear to have either overlapping or synergistic toxicities, and there are neither data nor theoretical concerns suggesting that co-administration of these drugs would result in increased toxicity compared with administration of either drug alone 14,27 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis found that exposure to PPI for patients receiving antiplatelet therapy was associated with a significant reduction in adverse GI events . However, there is some evidence of a potential drug interaction between clopidogrel and PPIs …”
Section: Introductionmentioning
confidence: 99%